Physicochemical and biological activity studies on complexes of some transition elements with mixed ligands of glycine and urea - Al-Maqtari, Maher Ali; Kassem Al-Qadasy, Mohammed; Mosa’d Jamil, Yasmin; Mohammed Al-Azab, Fathi; A. Al-Gaadbi, Amani (Eclética Química, 2018)
The reaction of urea (ur) and glycine (gly) with the metal ions Co(ΙΙ), Ni(ΙΙ) and Cu(ΙΙ) in ethanolic solution of 1M:1L1:1L2 molar ratio (where M= Co(II), Ni(II) and Cu(II), and L1 = urea L2 = glycine) led to the preparation of complexes of the general formula [M(ur)(gly)(H2O)2]Cl. Elemental microanalysis (CHN), molar conductivity measurements, IR,1HNMR, Mass and UV-VIS spectroscopic, and magnetic susceptibility measurements were used for the characterization of the compounds. Thermal analyses were used for the complexes degradation characterization. The complexes have an octahedral geometry and are of electrolytic nature in DMSO solvent with the absence of inner-sphere coordination of the chloride anion. An inhibition zone was observed for Ni-urea-glycine complex against Escherichia coli when the biological activity was considered.